Strategi Penetapan Tarif Rawat dalam Meningkatkan Income dan Angka Kunjungan Pasien Klinik Mitra Tamzil di Kabupaten Sukabumi - Rubadhiansyah, Mega Tamzil; Andriani, Rian; Santoso, Budi (Innovative: Journal Of Social Science Research, 2025)
This research aims to provide knowledge about. (1) unit level activity calculation strategy, (2) batch level activity calculation strategy, (3) product level activity calculation strategy, (4) facility level activity calculation strategy. By applying the ABC Method, the calculation results obtained are more accurate because they include all types of variables in determining the cost of production so that it is hoped that the profit that can be generated from production will be maximized. The clinic, using the Activity Based Costing (ABC) method, can trace the activities that occur in providing inpatient services, so that a reasonable cost can be determined. This research is a type of qualitative research. The type of data used in this research is qualitative data obtained through interviews, observation and documentation. The data analysis technique used is descriptive analysis. The results of the research using the Activity Based Costing (ABC) system, the lotus class (VIP) calculation using the ABC method is higher but still below the price of competitors around the Mitra Tamzil Clinic, Sukabumi Regency. And for other room rates using the ABC method, it is lower than the traditional calculation method currently in effect. The clinic can use the Activity Based Costing (ABC) method to find out strategies for increasing income and the number of patient visits at the Mitra Tamzil Clinic, Sukabumi Regency.